2017
DOI: 10.1093/cvr/cvx067
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant protein-D deficiency suppresses systemic inflammation and reduces atherosclerosis in ApoE knockout mice

Abstract: SP-D deficiency reduces atherosclerosis in part by decreasing the accumulation and proliferation of macrophages and by reducing IL-6 levels systemically. SP-D is a promising therapeutic target for cachectic COPD patients with elevated circulating SP-D levels who are at increased risk of cardiovascular morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 48 publications
0
25
0
Order By: Relevance
“…A subsequent study using double-deficient apolipoprotein E ( Apoe ) −/− Sftpd −/− mice showed similar quantitative effects in decreasing lesion size. Moreover, Sftpd deficiency resulted in less macrophage accumulation, and more smooth muscle cell coverage of lesions ( 457 ). In that study, endogenous SP-D reduced several plasma lipid fractions, including total cholesterol and induced circulatory IL-6, rather than TNF-α.…”
Section: Sp-d In Non-respiratory Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…A subsequent study using double-deficient apolipoprotein E ( Apoe ) −/− Sftpd −/− mice showed similar quantitative effects in decreasing lesion size. Moreover, Sftpd deficiency resulted in less macrophage accumulation, and more smooth muscle cell coverage of lesions ( 457 ). In that study, endogenous SP-D reduced several plasma lipid fractions, including total cholesterol and induced circulatory IL-6, rather than TNF-α.…”
Section: Sp-d In Non-respiratory Diseasesmentioning
confidence: 99%
“…The simplified overview of cellular functions in atherogenesis was inspired by Skaggs et al ( 458 ). Effects of SP-D in a long-term diet-induced model of atherosclerosis include (1) repression of high-density lipoprotein (HDL)-cholesterol levels ( 48 ) and also additional plasma lipid levels in a genetic model ( 457 ); (2) model-dependent induction of tumor necrosis factor-α (TNF-α) in vivo ( 48 , 457 ) and TNF-α induction in monocytes in vitro , dependent on osteoclast-associated receptor (OSCAR) signaling ( 133 ); (3) induction of macrophage proliferation ( 457 ); (4) induction of circulating monocytes; (5) decreased coverage of smooth muscle in plaques ( 457 ); (6) the result is an overall increase in atherosclerotic plaque formation with accumulation of foam cells and cholesterol crystals, accompanied by disturbed plasma lipid levels in Sftpd −/− mice compared with Sftpd +/+ mice ( 48 , 457 ). Moreover, TNF-α and NO increase endothelial SP-D expression ( 63 ) and circulating SP-D is increased in clinical cardiovascular disease (CVD) ( 25 , 429 ).…”
Section: Sp-d In Non-respiratory Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the relationship between SP-D and monocytes remains unclear, Jiang et al reported that depletion of circulating monocytes by intravenous injection of CL 2 days before intratracheal lipopolysaccharide (LPS) treatment significantly reduced SP-D in the lungs of mice treated with intratracheal LPS for 2 days (27) and Hirano et al reported that SP-D deficiency reduced blood monocytes in atherosclerosis-prone apolipoprotein E-knockout mice (28) . We therefore considered that elevation of SP-D was involved in the elevation of monocytes, and that the development of fibrosis associated with monocyte activation played a role in the relapse of OP.…”
Section: Discussionmentioning
confidence: 99%
“…We used C57BL/6 female mice that were purchased from CLEA Japan. SP-D knockout mice were kindly provided by Dr Don D. Sin in Vancouver, Canada ( 16 ). DNA was extracted from tail biopsies of mice using DNeasy blood and tissue kit (Qiagen, Inc.), according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%